Stomach bugs: What’s new in 2024 - K. Lehr; C. Thon; M. Ebert; A. Link (Microbiota in Health and Disease)
Many open questions remain about the microbes in the stomach, an environment long considered inhospitable. Our understanding of the gastric environment has been revolutionized over the last four decades by the identification of Helicobacter pylori (H. pylori). Despite significant advances, we are still unraveling the complex interactions within this ecosystem and identifying new microbial players in the acidic environment. In this review, we summarize the annual knowledge on the gastric microbiota published from 2023 to 2024, providing a comprehensive overview of the latest findings. Recent data shed light on the dynamics of the microbiome in the healthy state, as well as after H. pylori eradication and antibiotic resistance. Research on the microbiome in gastric cancer is revealing information about microbiota transitions during cancer progression and the potential role of the microbiome in assessing disease phenotype. The evidence surrounding Fusobacterium nucleatum (F. nucleatum) provides strong support for its clinical impact, although other bacteria and viruses also contribute. We look forward to further developments in this area, particularly in translating knowledge into clinical practice to improve the diagnosis and treatment of gastric diseases.